2012
DOI: 10.7155/jgaa.00253
|View full text |Cite
|
Sign up to set email alerts
|

Vertex Intersection Graphs of Paths on a Grid

Abstract: We investigate the class of vertex intersection graphs of paths on a grid, and specifically consider the subclasses that are obtained when each path in the representation has at most k bends (turns). We call such a subclass the B k -VPG graphs, k ≥ 0. In chip manufacturing, circuit layout is modeled as paths (wires) on a grid, where it is natural to constrain the number of bends per wire for reasons of feasibility and to reduce the cost of the chip.If the number k of bends is not restricted, then the VPG graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
77
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 20 publications
2
77
0
Order By: Relevance
“…Our main contribution is that every planar graph is B 2 -VPG (disproving the conjecture of Asinowski et al [3]). This result consists of the following interesting components.…”
Section: Introductionmentioning
confidence: 84%
“…Our main contribution is that every planar graph is B 2 -VPG (disproving the conjecture of Asinowski et al [3]). This result consists of the following interesting components.…”
Section: Introductionmentioning
confidence: 84%
“…Asinowski et al [3] showed that the class of VPG-graphs is equivalent to the class of graphs admitting a string-representation. They also defined the class B k -VPG, which contains all VPGgraphs for which each vertex is represented by a path with at most k bends (see [20] for the determination of Copyright © 2018 by SIAM Unauthorized reproduction of this article is prohibited 172 Downloaded 03/24/19 to 52.247.194.177.…”
Section: Introductionmentioning
confidence: 99%
“…A graph is said to be simply a VPG graph if it is a B k -VPG graph for some k. Several relationships between VPG graphs and other known graph classes have been studied in [ACG + 11]. VPG graphs are known to be equivalent to the known class of string graphs, which are the intersection graphs of simple curves in the plane [ACG + 12]. B 0 -VPG graphs are a special case of segment graphs (intersection graphs of line segments in the plane), which are known as 2-DIR graphs.…”
Section: Introductionmentioning
confidence: 99%